TIDAK DITERAPKANNYA PASAL 362 KUHP DALAM PERKARA PENAMBANGAN TANPA IZIN (STUDI PUTUSAN NOMOR 124/PID.SUS/2021/PN. TDN) - Achmadi, Cika Artika (Legal Standing : Jurnal Ilmu Hukum, 2023)
Mining activities cannot be carried out haphazardly because every business entity or individual must have a mining permit. Anyone who engages in illegal mining will be subject to sanctions in accordance with Article 158 of Law Number 3 of 2020 concerning "Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining". Mining without a permit (PETI) is a crime against State assets in the form of theft of minerals, in which the crime ignores the provisions in the mining procedure. The purpose of this paper is to investigate the factors considered by judges in deciding a case and the reasons why Article 362 of the Criminal Code is not used by prosecutors and judges in cases involving the theft of minerals. This research method is normative juridical law research, with an analytical approach method. This study uses secondary data sources. The data analysis technique used in this study uses qualitative data analysis. The results of the study show that the judge must first consider the indictment submitted by the prosecutor in court, because the judge cannot investigate or prosecute outside the scope of the indictment. In Decision Number 124/Pid.Sus/2021/Pn Tdn it is correct because the judge considers the facts and legal statements inside and outside the trial, so the Prosecutor and Judge do not apply Article 362 of the Criminal Code because there is a special law that deals with Mineral and Coal Mining.